"Camouflaging" by adolescent autistic girls who attend both mainstream and specialist resource classes: Perspectives of girls, their mothers and their educators. (October 2021) - Halsall, Joanne; Clarke, Chris; Crane, Laura
Autistic girls' heightened social motivation and associated social coping strategies, such as camouflaging, mean they may be less likely to receive appropriate support in mainstream schools. In this research, a multi-informant approach was used to examine the camouflaging strategies used by autistic girls within specialist resource classes attached to mainstream schools (whereby girls transition between resource classes and mainstream classes). Semi-structured interviews were conducted with eight adolescent girls, their parents (eight mothers) and their educators (six teaching assistants/aides and one senior staff member) about the girls' camouflaging experiences. Using reflexive thematic analysis, four themes were identified: (1) inconsistencies and contradictions in camouflaging, (2) challenges of relationships and 'finding a tribe', (3) learning, inclusion and awareness and (4) consequences of camouflaging. These results highlight the challenges that the girls experienced when attempting to hide their autism and fit within both mainstream classes and specialist resource classes. These challenges had significant impacts on the girls' relationships and learning, as well as consequences for their mental health. The findings highlight the need for increased awareness of how camouflaging presents across the autism spectrum and suggests that individualised, evidence-based support will be essential for enabling autistic girls to flourish in school. Lay abstract: There are a range of different types of schools that support children diagnosed with autism, including mainstream schools (where pupils are taught in general classrooms) and specialist schools (where pupils are exclusively taught alongside other children with special educational needs). An intermediary option involves resource bases attached to mainstream schools, which enable children to transition between mainstream and specialist educational settings. Autistic girls use a variety of strategies to negotiate the expectations and demands of school life. One of these strategies is known as camouflaging. This involves 'hiding' autism-based behaviours and developing ways to manage social situations, with the aim of fitting in with others. Research has shown that camouflaging can help to meet social expectations and friendships, but it can also result in challenges, including exhaustion and anxiety. In this study, we conducted detailed interviews with eight autistic girls, their parents and their school staff. The results showed that the girls tried to use camouflaging strategies to hide their autism and learning needs, especially within mainstream classrooms. Their camouflaging was often unsuccessful, which affected their relationships and sense of belonging. They also found camouflaging exhausting and distressing, which may (when combined with the demands of the classroom) affect their relationships, learning and mental health. This research provides important implications for supporting autistic girls who attend resource bases. These focus around increasing awareness of camouflaging and ways to support autistic girls, so they are included and able to fully participate and learn within school.